Indirect effect of hydrogen bonds on the magnetic coupling on Mn(iii) dinuclear compounds. Issue 41 (8th October 2018) - Pagès, J. M.; Escriche-Tur, L.; Font-Bardia, M.; Aullón, G.; Corbella, M.
Abstract : Hydrogen bonds between the cationic complex and counteranion weaken the antiferromagnetic interaction. Abstract : The Mn(iii ) dinuclear compounds [Mn(bpy)(H2 O)(μ-2, 6-Cl2 C6 H3 COO)2 (μ-O)Mn(bpy)(X)]X, where X = ClO4 (1 ) or X = NO3 (2 ), were synthesised and characterised by X-ray diffraction spectroscopy. In both cases there were hydrogen bond interactions between the aqua ligand and counteranions, but with different connectivity patterns. For compound1, the interactions connected two dinuclear complexes through two perchlorate counteranions to generate a tetranuclear unit. For compound2, the hydrogen bond was "intramolecular" between the cationic complex, nitrate counteranion and crystallization water (Mn–LW ⋯NO3 − ⋯H2 O⋯LN –Mn). This unusual interaction was responsible for the perfect orthogonality of the coordination octahedra on the dinuclear entity and noticeable elongation of these polyedra. Both compounds showed antiferromagnetic coupling, which was unusually strong for compound2 with a nitrate anion ( J = −9.2 and −27.3 cm −1 for1 and2, respectively) ( H = − J · S 1 · S 2 ). The effect of the counteranion (X) on the magnetic interaction was analysed by density functional theory studies. For both compounds, hydrogen bonds between the aqua ligand and counteranions weakened the antiferromagnetic interaction. Moreover, for2, replacement of the counteranion nitrate with other groups had a significant effect on the magnetic interaction.